Analysis of Halal Industry Development in Padangsidimpuan City - Guci, Sari Wildani Guci; Chuzaimah Batubara; Juliana Nasution (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The halal industry in Padangsidimpuan City has significant potential to develop, especially in the food and beverage sector, along with increasing public awareness of the importance of halal products. This study aims to analyze the dynamics and challenges faced by business actors, especially Micro, Small, and Medium Enterprises (MSMEs), in developing the halal industry. Through a qualitative approach and SWOT analysis, this study identifies the strengths, weaknesses, opportunities, and threats that affect the halal industry in the area. The results of the study indicate that support from the government and related institutions is very important to assist business actors in the halal certification process and increase the competitiveness of halal products in local and international markets. The resulting policy recommendations are expected to encourage the development of a more integrated and sustainable halal industry in Padangsidimpuan City